Using nestling plasma to assess long-term spatial and temporal concentrations of organochlorine compounds in bald eagles within Voyageurs National Park, Minnesota, USA. (March 2015) - Pittman, H. Tyler; Bowerman, William W.; Grim, Leland H.; Grubb, Teryl G.; Bridges, William C.; Wierda, Michael R.
Highlights: Polychlorinated biphenyls (PCBs) are decreasing in Voyageurs National Park (VNP), MN. Most organochlorine pesticides are decreasing in Voyageurs National Park (VNP), MN. Dieldrin concentrations in bald eagle nestling blood plasma are increasing. Dieldrin concentrations may be tied to a new source or environmental processes. Abstract: The bald eagle ( Haliaeetus leucocephalus ) population at Voyageurs National Park (VNP) provides an opportunity to assess long-term temporal and spatial trends of persistent environmental contaminants. Nestling bald eagle plasma samples collected from 1997 to 2010 were analyzed for polychlorinated biphenyls (PCBs) and organochlorine pesticides. Trends of total PCBs, total DDTs, 4, 4′-DDE, and Dieldrin were analyzed since >50% of nestling plasma samples had detectable concentrations. Total PCBs, total DDTs, and 4, 4′-DDE concentrations have all decreased over time (26.09%, 24.09%, and 40.92% respectively). Concentrations of Dieldrin have increased by 50.25%. In this study, 61.1% of all nestlings sampled had detectable concentrations of Dieldrin from all time periods and all areas of VNP. Since Dieldrin is a banned pesticide in North America, the source of this increase is unknown. However, increases and fluctuations in Dieldrin concentration suggest contaminant levels in VNP may be linked to a new source or environmental process.